A new low-profile inverted A-shaped patch antenna for multi-band operations - Ahsan, M.R.; Islam, M.T.; Ullah, M.H. (2015)
This paper presents the design and analysis of a compact modified inverted-A shape multi-band patch antenna for WiMAX and C-band telecommunication satellite applications. The proposed antenna has simple geometrical structure which consist of 20 mm x 20 mm radiating patch with slot loading and fed by 4 mm long microstrip line. The proposed antenna is designed and analyzed by using commercially available full-wave 3D high frequency electromagnetic simulator namely Ansys HFSS. The optimized design of the proposed multi-band patch antenna is fabricated on 1.6 mm thick fiberglass polymer resin dielectric material substrate with reduced ground plane by using in-house PCB fabrication machineries and antenna performances are measured in a standard far field anechoic chamber. From the experimental results it is observed that, the antenna prototype has achieved operating bandwidth (return loss - 10dB) 360 MHz ( GHz) and 440 MHz ( GHz) for WiMAX and, 1550 MHz ( GHz) for C-band. The measured maximum radiation gains for the antenna are about 3.62 dBi, 3.67 dBi and 5.7 dBi at lower, middle and upper operating bands respectively. The designed antenna shows good radiation characteristics and appreciable gain over the operating bands which make it a reliable candidate for WiMAX bands and C-band applications.